2016
DOI: 10.5194/acp-16-8667-2016
|View full text |Cite
|
Sign up to set email alerts
|

A semi-empirical model for mesospheric and stratospheric NO<sub><i>y</i></sub> produced by energetic particle precipitation

Abstract: Abstract. The MIPAS Fourier transform spectrometer on board Envisat has measured global distributions of the six principal reactive nitrogen (NO y ) compounds (HNO 3 , NO 2 , NO, N 2 O 5 , ClONO 2 , and HNO 4 ) during 2002-2012. These observations were used previously to detect regular polar winter descent of reactive nitrogen produced by energetic particle precipitation (EPP) down to the lower stratosphere, often called the EPP indirect effect. It has further been shown that the observed fraction of NO y prod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 43 publications
(76 reference statements)
4
37
0
Order By: Relevance
“…These lags for Ap are thus employed in all analyses. Similar time lags were already previously found optimal (Maliniemi et al, , ; Salminen et al, ) and agree with the time it takes for majority of NO x /NO y created by energetic particle precipitation to descend from the mesosphere to the stratosphere (Funke et al, , ). Note that these lags also correspond well to the effective lags, which Funke et al () found optimal for correlation between EPP produced NO y in the stratosphere/lower mesosphere and the Ap index.…”
Section: Methodssupporting
confidence: 89%
“…These lags for Ap are thus employed in all analyses. Similar time lags were already previously found optimal (Maliniemi et al, , ; Salminen et al, ) and agree with the time it takes for majority of NO x /NO y created by energetic particle precipitation to descend from the mesosphere to the stratosphere (Funke et al, , ). Note that these lags also correspond well to the effective lags, which Funke et al () found optimal for correlation between EPP produced NO y in the stratosphere/lower mesosphere and the Ap index.…”
Section: Methodssupporting
confidence: 89%
“…In other cases, a simple parameterization in dependence of the seasonally averaged Ap index (Baumgaertner et al, 2009) was employed (e.g., Baumgaertner et al, 2011;Rozanov et al, 2012), enabling extended simulations over multidecadal time periods. We recommend the use of the UBC model described in Funke et al (2016) which is designed for the latter application and represents an improved parameterization due to its more detailed representation of geomagnetic modulations, latitudinal distribution, and seasonal evolution. This semi-empirical model for computing time-dependent global zonal mean NO y concentrations (in units of cm −3 ) or EPP-NO y molecular fluxes (in units of cm −2 s −1 ) at pressure levels within 1-0.01 hPa is available at http://solarisheppa.geomar.de/solarisheppa/cmip6.…”
Section: The Epp Indirect Effect: Odd Nitrogen Upper-boundary Conditionmentioning
confidence: 99%
“…Geomagnetic forcing of NO y in the mesosphere is considered by applying an upper boundary condition (UBC) of NO y , parameterized by the geomagnetic Ap index (newly developed submodel UBCNOX). This applies an online version of the upper boundary condition for the amount of NO x described in Funke et al (2016) and Matthes et al (2017). All three parts of the parameterization (background, energetic particles and elevated stratopause events (ESEs)) are calculated directly on the model grid.…”
Section: Emacmentioning
confidence: 99%
“…Additionally, all models carried out one scenario including full particle forcing as available to the respective model: 3dCTM including protons and electrons from AIMOS model v1.6 and photoionization (v1.6 phioniz); KASIMA including protons and electrons from AIMOS model v1.6 (v1.6); and EMAC including protons from the database and NO y upper boundary conditions as a constraint for the EPP indirect effect (UBC, Funke et al, 2016).…”
Section: Model Experimentsmentioning
confidence: 99%
See 1 more Smart Citation